Stakeholder theory, industrial revolution, and interaction models on the internet: further research topics: - Hermansyah Andi Wibowo (Institute of Computer Science (IOCS), 2023)
As an ethical-based theory of moral philosophy, stakeholder theory inherits problems in its function of explaining recent business activities. This is because there is an assumption that the characteristics of the environment can direct the development of organizational theory. Epistemologically, Stakeholders Theory provides opportunities for researchers across disciplines and fields of study to be involved in its development. Therefore, the authors offer a thesis about the involvement of business environment characteristics to the development of theory. This thesis is axiomatic but actually taken for granted by researchers. Content analysis was chosen as the main method by collecting articles using www.google.com and www.scholar.google.com as well as PoP software. Source in the form of video transcripts from interviews with stakeholder theorist R. Edward Freeman was also analyzed. The characteristics of the two concepts, namely the industrial revolution 4.0 and stakeholder theory are explained and concluded which in the end the synthesis between the two concepts is visualized. This article then discusses the results of the visualization in the form of an interaction model, to support this research thesis and to provide a contribution in the future research topics.